Planar Defects Impact on Non-fundamental Efficiency Losses in mc-Si Solar Cells - Prykhodko, A. V.; Приходько, Олександр Васильович (SSU, 2019)
Planar defects can severely limit the efficiency of multicrystalline silicon (mc-Si) solar cells for a lot of reasons. The impact of grain boundaries, twins and stacking faults on fill factor losses in mc-Si solar cells has been studied. No any clear influences of planar defects presence on parasitic resistances and minority carrier lifetime were observed. The mechanism resulting in an increase of recombination component of p-n junction saturation current due to the Suzuki interaction of stacking faults with some metal traces was proposed. The possibilities for useful stacking fault engineering during ingot solidification, its cutting and wafering were discussed. No grain boundary, twin and stacking fault effects on solar cell efficiency losses due to parasitic ohmic resistances were observed. Stacking fault clusters with deformation origin that are capable of accumulating recombination impurities have been detected besides visually observed grain and twin boundaries. When angles between planes of stacking faults and p-n junction are small, the most of depleted layers are occupied by them and recombination component of the saturation current increases significantly that results in the enhancement of efficiency losses.
Keywords: Solar cell; mc-Si; Fill factor; Parasitic ohmic resistance; Dark saturation current; Diode ideality factor; Grain boundary; Stacking fault; Twin